IOS and OS X network programming cookbook : over 50 recipes to develop network applications in both the iOS and OS X environment - Hoffman, Jon (Quick answers to common problems, 2014)
This book follows a recipe-based approach that will heavily focus on the code and how to integrate the samples with the reader's projects. Each recipe consists of one or more methods that you can put directly into your app and use. This book is ideal for developers that want to create network applications for the Apple OS X or iOS platforms. All examples are written in Objective-C using XCode as the IDE. Knowledge of Objective-C and X-Code is essential.